Mapas do encontro: estudos da relação comunicativa corpo - cidade - Neves, Heloisa (2007)
The objective of this master dissertation is study a specific type of map, which means meeting map . This object investigates how happens and how it representates the communication between people and cities. This study starts from the discussion of the representation and perception actions, according to how these things are being study nowadays by transdisciplie net, who build the theory of this research. The main point of debate were discussion about emotion, feelings and body images done by António Damásio (1999, 2003); the concept of enaction proposed by Francisco Varella; the differences between map and decal proposed by Gilles Deleuze e Felix Guattari (1999); and the concept of corpomidia , mainly about communication process involved in body relation with the environment proposed by Greiner e Katz (2005). The research results were a bibliographical revision about what means create a map and some reading made from diverse kind of medias (movies, installations and press), as well as experiments that takes body signs impressions at the moment that the body is exposed to the citie´s own image, when a perceptive meeting action happens. Later, these signs were decode into images and sounds that lead us to the creation of a meeting map between body and city. Part of this research was developed in Lima (Peru) in the biotechnology laboratory and in the Centro de Investigación de la Arquitectura y la Ciudad (CIAC) of Pontifícia Universidade Católica